2020
DOI: 10.3390/ijerph17103627
|View full text |Cite
|
Sign up to set email alerts
|

Application of Geophysical and Hydrogeochemical Methods to the Protection of Drinking Groundwater in Karst Regions

Abstract: To provide theoretical support for the protection of centralized drinking groundwater sources in karst areas, it is necessary to accurately identify the development of karst conduits and analyze the differences in hydrogeochemical characteristics of different karst systems. This provides a scientific basis for the accurate designation of risk zones that may cause drinking groundwater pollution. In this study, a geophysical survey, hydrogeological chemical process analysis and optimized fuzzy cluster analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Additionally, source–process–end control measures should be implemented to ensure the future safety of groundwater drinking sources distributed further downstream of the landfill. In view of the limited migration distance of pollutants in the red-bed area, the landfill can be closed in situ by using a coverage system to minimize the generation and infiltration of leachate [ 61 , 62 ]. The aquifer will act as a natural treatment plant to naturally attenuate pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, source–process–end control measures should be implemented to ensure the future safety of groundwater drinking sources distributed further downstream of the landfill. In view of the limited migration distance of pollutants in the red-bed area, the landfill can be closed in situ by using a coverage system to minimize the generation and infiltration of leachate [ 61 , 62 ]. The aquifer will act as a natural treatment plant to naturally attenuate pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…From Table 6 6 revealed that sample locations GT-1 and 21 is classified to be of deep meteoric water percolation type that implies that the groundwater is influenced by precipitation [47] . While sample locations GT-2, 3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,22,23,24,25,26,27,28,29,30,31,32,33 and 34 fell within shallow meteoric water.…”
Section: Gibbs Plotmentioning
confidence: 99%
“…Preliminary information and criteria for decision-making in such areas as designation of land use controls, delineation of monitoring networks and management of water resources in the context of regional planning are related to protection of groundwater quality [5] . Several reports by various scholars have proven that the combination of VES and hydrogeochemical studies is to considered successful in assessment of groundwater vulnerable to surface contamination in sedimentary and hard rock terrain [6][7][8][9] . [10,11] were of the opinion, that the VES is one of the geoelectrical method mostly used in measuring the vertical alterations of electrical resistivity of rock unit.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a high resistivity anomaly is seen at a depth of 300 m to 350, interpreted as massive limestone. According to the study [22], the karst limestone has been deformed due to karstification.…”
Section: -Medium Resistivitymentioning
confidence: 99%